Congress and the presidency: their role in modern times - Schlesinger, Arthur M.; De Grazia, Alfred (Washington D.C.: American Enterprise Institute for Public Policy Research, 1967)
This book offers comprehensive coverage of the U.S. Congress and the legislative process by looking at the tension between Congress as a lawmaking institution and as a collection of re-election-minded politicians.
First in the series of Rationale debate seminars held at George Washington University, Washington, D.C., during the 1966-67 academic year.
Bibliographical references included in "Footnotes" (p. [191]-192)
aia 19/10/2018
Keywords: Executive power